Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1159/000327036
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol in Acute Ischemic Stroke Treatment (CAIST Trial): A Randomized Double-Blind Non-Inferiority Trial

Abstract: Background: Aspirin is a proven antiplatelet agent in acute ischemic stroke, and there are no current guidelines for other antiplatelet treatments. We aimed to compare the efficacy and safety of cilostazol with aspirin in acute stroke. Methods: Patients with measurable neurological deficits (NIHSS score ≤15) within 48 h of onset were randomly assigned to cilostazol (200 mg/day) or aspirin (300 mg/day) for 90 days. The primary endpoint was a modified Rankin Scale (mRS) score of 0–2 at 90 days. Cardiovascular ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 44 publications
(35 reference statements)
1
58
0
1
Order By: Relevance
“…It significantly reduced the rate of recurrent stroke and had lower hemorrhagic events compared with aspirin in the CSPS 2 trial in Japan. 15,19, 20 Our results similarly showed that cilostazol significantly reduced (21%) the risk of ischemic stroke, with similar safety to aspirin for Taiwanese patients with PAD and CVD. We consider that the Abbreviations as in Tables 1-3.…”
Section: Discussionsupporting
confidence: 66%
“…It significantly reduced the rate of recurrent stroke and had lower hemorrhagic events compared with aspirin in the CSPS 2 trial in Japan. 15,19, 20 Our results similarly showed that cilostazol significantly reduced (21%) the risk of ischemic stroke, with similar safety to aspirin for Taiwanese patients with PAD and CVD. We consider that the Abbreviations as in Tables 1-3.…”
Section: Discussionsupporting
confidence: 66%
“…Use of PDE inhibitors in the early postischemic phase is currently not recommended due to a possibly increased bleeding risk by PDEinduced platelet inhibition. However, a recently completed clinical trial with cilostazole (CAIST: Cilostazol in acute ischemic stroke treatment (Lee et al, 2011)) showed that cilostazol is comparable to aspirine in terms of safety and bleeding complications so further clinical evaluation of cilostazol mono-or combination-therapy in acute stroke is ongoing (Nakamura et al, 2011).…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 99%
“…Second, considering the etiological heterogeneity of acute hearing loss and tinnitus, administration of cilostazol for acute vascular insufficiency may have a role in the treatment of acute tinnitus. Indeed, clinical trials of cilostazol have shown beneficial effects on treatment for acute cardiovascular disease, acute renal dysfunction, and acute ischemic stroke [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…In two large prospective clinical studies of cilostazol, the incidences of headache development were reported to be 24% and 50.6% [29,31] . According to recent studies, cilostazol induced migraine-like headache in most of the participants without any history of migraine, and this phenomenon is believed to be due to intracellular cAMP accumulation [33,34] .…”
Section: Discussionmentioning
confidence: 99%